Diverging Trends in Worker Health and Safety Protection and Participation in Canada, 1985-2000 - Tucker, Eric (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryDespite the comprehensiveness of neo-liberal restructuring in Canada, it has not proceeded uniformly in its timing or outcomes across regulatory fields and political jurisdictions. The example of occupational health and safety (OHS) regulation is instructive. This article compares recent OHS developments in five Canadian jurisdictions, Alberta, British Columbia, Nova Scotia, Ontario and the Federal jurisdiction. It finds that despite the adoption of a common model by all jurisdictions, there has recently been considerable divergence in the way that the elements of worker participation and protection have been combined. Modified power resource theory is used to explain a portion of this divergence.